SE translation mRNA overexpression: a potential prognostic predictor in breast cancer - Du, Qian; Hao, Ruifang; Liu, Leichao; Liu, Yang; Chen, Siying; You, Haisheng; Zhang, Ying; Dong, Yalin (Translational Cancer Research, 2019)
Background: Patient SE translation (SET) belongs to histone chaperone nucleosome assembly protein family and has been confirmed that it is associated with carcinogenesis, tumor progression and patient outcome. In this study, we aim at assessing the prognostic value of SET mRNA, the function and pathway of SET and its related genes in breast cancer. Methods: The clinicopathological and prognostic significance of SET was assessed by the molecular taxonomy of breast cancer international consortium (METABRIC) database (n=1,904). Additionally, based on the data and network of SET and its related genes from cBioPortal website, their function in the progression of breast cancer was also explored. Results: SET mRNA overexpression was a significant predictor of a poor prognosis (P=0.0006). The two signaling pathways associated with SET were the facilitating function of condensin II on mitosis and the accelerated transportation of tumor cell mRNA towards the extranuclear position, and SET acted to suppress condensin II and stabilize mRNA. Conclusions: Owing to the regulation of chromosome condensation and stabilization of tumor cell mRNA, overexpression of SET is correlated with aggressive phenotypes and facilitates tumor proliferation and deterioration. SET may act as a valuable prognosis biomarker in breast cancer.